Patient safety culture according to nursing professionals of an accredited hospital - Eliana Melo; Alexandre Pazetto Balsanelli; Vanessa Ribeiro Neves; Elena Bohomol (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To evaluate the perception of the nursing team regarding the patient safety culture of an accredited hospital and to identify the differences between shifts, professional category and units. Method: Cross-sectional study, conducted in a private hospital in the city of São Paulo, SP, Brazil, with application of the Survey on Patient Safety Culture Hospital to 497 nursing professionals. Descriptive analysis, instrument consistency and generalized linear mixed model were performed. Results: The organizational learning and continuous improvement dimension was considered a strong area (77%) and the personal adequacy (47%), shift / shift change and transfer (47%) and non-punitive response to errors (25%) dimensions were considered. fragile. Differences in perception were found between the professional categories in two dimensions; between shifts in six and between units in seven dimensions. Conclusion: The nursing team identified weaknesses in the patient safety culture in the hospital, with the need to standardize the improvement processes.